Middleware de segurança adaptativo para computação móvel - Bruno Pontes Soares Rocha (2007)
The mobile computing paradigm has introduced new problems for application developers. Challenges include heterogeneity of hardware, software, and communication protocols, resource limitations and varying wireless channel quality. In this scenario, security becomes a major concern for mobile users and applications. Security requirements for each application are different, as well as the hardware capabilities of each device. To make things worse, wireless medium conditions may change dramatically with time, incurring great impact on performance and QoS guarantees for the application. Currently, most of the security solutions for mobile devices use a static set of algorithms and protocols for services such as cryptography and hashes.In this work we propose a security service, which works as a middleware, with the ability to dynamically change the security protocols used between two peers. Changes are made according to variations on the wireless medium parameters and system resource usage, hardware resources, application-defined QoS metrics, and desired security levels''. We also present an extension that allows our middleware to consider the semantic value of packets being transmitted in order to choose the best protocols to be used. We compare our solution to some widespread static security protocols and show how our middleware is able to adapt itself over different conditions of medium and system.